The role of the Bureau of Government and Regional Autonomy in facilitating the preparation of regional government accountability reports within the West Sumatra Provincial Government - Achmad Ikhlas; Rizki Syafril (Priviet Social Sciences Journal, 2026)
The implementation of regional governance in the era of bureaucratic reform requires governance that is transparent, accountable, effective, efficient, and service-oriented. Public accountability in regional governments is reflected in the Regional Head Accountability Report or Laporan Keterangan Pertanggungjawaban (LKPJ), submitted annually by the regional head to the Regional House of Representatives or Dewan Perwakilan Rakyat Daerah (DPRD). The preparation of the LKPJ requires the coordination, synchronization, and harmonization of data from all Regional Apparatus Organizations or Organisasi Perangkat Daerah (OPD) to ensure that the report is objective and in accordance with regulations. This study aims to analyze the role of the Bureau of Government and Regional Autonomy of the Regional Secretariat of West Sumatra Province in facilitating the preparation of LKPJ. This research employed a systematic literature review method, drawing on peer-reviewed academic sources, government regulations, and official policy documents relevant to public administration and regional accountability. The findings show that the bureau plays a strategic role as a coordinator, facilitator, verifier, and quality controller in the preparation of the LKPJ. Its responsibilities include coordinating regional apparatus organizations, verifying performance data, preparing technical guidelines, and harmonizing report substances with regional planning documents and regulations. However, several obstacles remain, including delays in data submission, limited digital information systems, differences in human resource capacity, and inconsistencies in inter-agency data synchronization.